Metagenomic inference of microbial community composition and function in the weathering crust aquifer of a temperate glacier - Faber, Quincy; Davis, Christina; Christner, Brent (Frontiers in Microbiomes, 2024)
Bacterial, fungal, and algal communities that colonize aquatic systems on glacial ice surfaces mediate biogeochemical reactions that alter meltwater composition and affect meltwater production and storage. In this study, we sought to improve understanding of microbial communities inhabiting the shallow aquifer that forms seasonally within the ice surface of a glacier’s ablation zone (i.e., the weathering crust aquifer). Using a metagenomic approach, we compared gene contents of microbial assemblages in the weathering crust aquifer (WCA) of the Matanuska Glacier (Alaska, USA) to those recovered from supraglacial features and englacial ice. High abundances of Pseudomonadota, Cyanobacteriota, Actinomycetota, and Bacteroidota were observed across all samples, while taxa in class Gammaproteobacteria were found at significantly higher abundances in the weathering crust aquifer. The weathering crust aquifer samples also contained higher abundances of Dothideomycetes and Microbotryomyetes; fungal classes commonly observed in snow and other icy ecosystems. Phylogenetic analysis of 18S rRNA and rbcL gene sequences indicated high abundances of algae in the WCA that are closely related (> 98% and > 93% identity, respectively) to taxa of Ancylonema (Streptophyta) and Ochromonas (Ochrophyta) reported from glacial ice surfaces in Svalbard and Antarctic sea ice. Many functional gene categories (e.g., homeostasis, cellular regulation, and stress responses) were enriched in samples from the weathering crust aquifer compared to those from proximal englacial and supraglacial habitats, providing evidence for ecological specialization in the communities. The identification of phagotrophic phytoflagellate taxa and genes involved in mixotrophy implies that combined phototrophic and heterotrophic production may assist with persistence in the low light, low energy, and ephemeral conditions of the weathering crust environment. The compositional and functional differences we have documented indicate distinct microbial distributions and functional processes occur in the weathering crust aquifer environment, and we discuss how deciphering these nuances is essential for developing a more complete understanding of ecosystem biogeochemistry in supraglacial hydrological systems.